Implementasi Kemampuan Literasi Sains dalam Pembelajaran IPA Terintegrasi di Sekolah Dasar - Ala Purnawati; Nurul Yakin (Lembaga Einstein College (LEC), 2025)
Science literacy has a very important role in integrated science learning because it is able to increase students' comprehensive understanding of science concepts and their application in daily life. To be able to develop and create a learning atmosphere that makes students actively involved in it. Teacher-centered learning makes students passive and easily saturated during the learning process. This saturation will later cause students to have no ability to reason and implement knowledge related to science literacy. The purpose of this study is to find out the implementation of science literacy skills in integrated science learning in elementary schools, improve scientific thinking skills, encourage students to understand the relationship between science concepts and help students relate science to real life and decision-making. The methods used in this study are literature studies and field observations and interviews. The literature studies obtained came from several articles related to the research, and were also obtained from the results of observations which were then concluded. The data were then analyzed qualitatively with descriptive elaboration. The results of the research obtained by science literacy skills can be With integrated science learning, students no longer study science separately (physics, chemistry, biology), but as a whole unit. Science literacy helps them in relating various concepts in one context, understanding the relationship between natural phenomena from various scientific perspectives. This strengthens the skills of the scientific process that are the core of science learning. With this implementation, developing critical and reflective thinking skills is very important in facing complex challenges and information in the digital era. In addition, it increases awareness of global issues and real life because science literacy directs science learning to be more relevant to daily life, so that students are more concerned and actively involved in solving environmental and social problems. The implementation of science literacy in integrated science learning provides a more contextual and meaningful learning experience for students. Approaches such as PBL, STEM, and scientific inquiry are highly effective in improving science literacy skills in integrated science learning